2003
DOI: 10.1634/theoncologist.8-4-342
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Female Long-Term Colorectal Cancer Survivors

Abstract: Although the number of women who survive treatment for colorectal cancer is growing, little is known about the quality of life of long-term survivors. The purpose of analyses presented in this paper is to describe the overall health-related quality of life of female long-term colorectal cancer survivors and the factors that may modify their levels of quality of life. A population-based sample of 726 Wisconsin women diagnosed with colorectal cancer from 1990-1991 was recontacted. Of the 443 women alive in 1999,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
2
7

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 42 publications
(55 reference statements)
9
64
2
7
Order By: Relevance
“…TSALIC et al (29) , em estudo prospectivo em 243 pacientes com câncer colorretal em uso das mesmas drogas e dosagens, observaram neutropenia febril em 12,2% e diarréia grau 3 e 4 em 8%. A toxicidade foi maior no sexo feminino.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…TSALIC et al (29) , em estudo prospectivo em 243 pacientes com câncer colorretal em uso das mesmas drogas e dosagens, observaram neutropenia febril em 12,2% e diarréia grau 3 e 4 em 8%. A toxicidade foi maior no sexo feminino.…”
Section: Discussionunclassified
“…A qualidade de vida foi infl uenciada signifi cativamente no período pós-operatório e a partir do 3 o mês os escores melhoraram. TRENTHAM-DIETZ et al (29) observaram entre as mulheres com câncer colorretal com idade mais avançada e maior número de co-morbidades, menores índices no domínio físico, utilizando o questionário SF-36.…”
Section: Discussionunclassified
“…36,37 For colorectal survivors, 1 follow-up of a large cohort of women with mean age of 72 years and mean survival length of 9 years documented no physical function differences between survivors and age-matched norms. 38 Not surprisingly, physical function declined as age and comorbidities increased. Because only broad QOL endpoints were measured, specific problem domains such as sexual, urinary, or bowel function could not be evaluated.…”
Section: Studies Within Specific Diseasesmentioning
confidence: 99%
“…In this study the physical component summary score was lower in older patients, in those with more co-morbidities, and in those with greater body mass index [30]. The mental component was lower in patients with more comorbidities [30].…”
Section: Quality Of Life After Colorectal Cancer Resectionmentioning
confidence: 41%
“…Another population based study where the SF-36 form was used in a sample of women (n ¼ 307) with colorectal cancer who were re-contacted 8-9 years after their diagnosis revealed that issues related to colorectal cancer diagnosis were not dominant in terms of QOL in female long term colorectal cancer survivors [30]. In this study the physical component summary score was lower in older patients, in those with more co-morbidities, and in those with greater body mass index [30].…”
Section: Quality Of Life After Colorectal Cancer Resectionmentioning
confidence: 99%